CIUR: relação entre o volume placentário anteparto por ecografia e pós-parto por macroscopia, e achados perinatais - Feltrin, Marcelo Lorensi (2016)
Introduction: fetal growth restriction, also called intrauterine growth restriction (IUGR) is a major complication of pregnancy. It is associated with high rates of perinatal morbidity and mortality and childhood, requiring high financial investments to enable adequate care for these newborns. Justification: need for a clinical and sonographic marker, through which one can predict the risk of a fetus likely to have impaired growth, enabling early, and better perinatal care intervention. Purpose: Check the relationship between the measure the placental volume obtained by antenatal ultrasonography, and immediately after birth by macroscopic in fetuses of pregnant women with suspected IUGR and low-risk pregnant women, and perinatal outcomes. Methods: Cross-sectional, prospective, observational study involving 30 low-risk pregnant women and 19 pregnant women of fetuses with suspected IUGR (weigth and/or waist circumference below the 10th percentile for gestational age), treated at Hospital Universitário de Santa Maria (HUSM). The antepartum placental volume, in cm3, was measured by the method described by Azpurua et al, which uses the measurements of length, height and thickness placenta; through the application provided by the same author, it was determined that percentile is the volume found for the given gestational age. The postpartum volume was measured by Archimedes Principle. Perinatal data were obtained from birth records and medical records of newborns. The measures of the variables were analyzed in the form of mean and standard deviation (parametric data), median and quartiles (nonparametric data). Statistical tests: t-Student, Mann-Whitney test, Pearson correlation; It was satisfactory a significance level of 5%, and the data stored and analyzed using the SPSS version 21.0. Results: There was a highly significant difference between the ultrasound and macroscopic placental volume in both groups (p<0,001); was a correlation between placental volume and Apgar in the first minute in the IUGR group (p<0,02); there was a highly significant association between admission to the neonatal intensive care unit, being higher in IUGR group (p<0,01); 94,7% of patients in the group IUGR had placentas with volume below the p10, used in the application. Conclusions: the volume of the placenta after delivery was lower than calculated before birth, in both groups, which is expected, due to the loss of blood through the placenta after placental delivery Adverse perinatal outcomes were present when the placental volume is small but that could be justified by prematurity. Thus, the findings of this study are suggestive of the placental volume in fetuses with IUGR is decreased and associated with few adverse perinatal outcomes. Studies with larger samples may confirm these assumptions.